Graphene-metal nanoparticles for enhancing thermoelectric power factor - Shiau, Li Lynn (2021)
Chemical vapor deposition (CVD) grown graphene has been reported for a myriad of nanoelectronics and nanophotonics applications. However, CVD grown graphene suffers from low electrical conductivity due to the presence of multiple grain boundaries and intragranular defects. In order to improve its performance, graphene is often functionalized with other materials. In this work, graphene was hybridized with metallic nanoparticles (Au, Ag and Pt). Metal-containing inorganic compound solution was drop casted onto patterned graphene and was subsequently reduced by ultraviolet light. The hybridized graphene systems were explored as possible thermoelectric generators. It was shown that nanoparticles hybridized graphene displayed a significant decrease in sheet resistance. Amongst them, Au-graphene revealed an 80% decrease in sheet resistance. Ag- and Pt-graphene did not show any enhancement in the Seebeck effect while Au-graphene observed a 25% decline due to the thermal cooling effect. Overall, thermoelectric power factor was shown to increase by a factor of 2.96, 1.72 and 1.25 times for Au-graphene, Ag-graphene, and Pt-graphene, respectively.